Effect of Methyl Jasmonate in Gene Expression, and in Hormonal and Phenolic Profiles of Holm Oak Embryogenic Lines Before and After Infection With Phytophthora cinnamomi - Morcillo, Marian; Sales, Ester; Corredoira, Elena; Martínez, María Teresa; Segura, Juan; Arrillaga, Isabel (Frontiers in Plant Science, 2022)
The dieback syndrome affecting Quercus ilex and other oaks species impels the search for tolerant plant genotypes, as well as methods of plant immunization against such infections. Elicitation treatments can be an effective strategy to activate plant defense response and embryogenic lines represent a promising tool to generate new tolerant genotypes and also to study early markers involved in defense response. The aim of the presented work was to investigate changes in gene expression, and in hormonal and phenolic profiles, induced in three holm oak embryogenic lines (EL) elicited with methyl jasmonate (MeJA), before and after infection with the oomycete Phytophthora cinnamomi, which is the main biotic agent involved in this pathogenic process. The three EL, derived from three genotypes, showed different basal profiles in all tested parameters, noting that the VA5 naïve genotype from a scape tree was characterized by a basal higher expression in NADPH-dependent cinnamyl alcohol dehydrogenase (CAD) and chalcone synthase (CHS) genes and also by higher caffeic acid content. Our work also identifies changes triggered by MeJA elicitation in holm oak embryogenic lines, such as increases in ABA and JA contents, as well as in levels of most of the determined phenolic compounds, especially in caffeic acid in Q8 and E00 ELs, but not in their biosynthesis genes. Irrespective of the EL, the response to oomycete infection in holm oak elicited plant material was characterized by a further increase in JA. Since JA and phenols have been described as a part of the Q. ilex defence response against P. cinnamomi, we propose that MeJA may act as an IR stimulus and that induced in our embryogenic material both direct (detected prior to any challenge) and primed (detected after subsequent challenge) defence responses.